Energetically self-sufficient robot group study kit - M. A. Rovbo; A. A. Malyshev (Открытое образование (Москва), 2017)
The article considers the project of educational and research software and hardware kit designed for use in case-based educational project activities based on the theme of energetically autonomous robots. An important feature of the complex is its interdisciplinarity since robotics combines many fields of science and technology — mechanical design, electronics, programming, elements of artificial intelligence, energy science and others. Students can receive basic knowledge in these areas as well as gain practical skills in solving real problems that require a convergent approach. The kit serves as an experimental basis that allows to study intricacies of robot control and its hardware and software design while making structural changes, including using different power units: solar, fuel, thermoelectric and others. Power units (converters and the various sources of renewable energy) may be considered both from the theoretical point of view, i.e. from the principles of their functioning and from the practical aspect — studying their practical application in real systems. Another important aspect of the system is the development of software architecture for a robot and for a team of robots as well as studying the interactions between them. In addition to performing the target task, ancillary tasks such as maintaining the battery level, communication with other team members in a multi-agent system, should be considered in the control algorithm of the robot, which allows to study the distribution of priorities between these objectives, as shown in the example of multicriteria optimization. The prototype of the kit and its usage according to the described approach have been partially validated by conducting computational experiments with algorithms based on different search methods (random search, closest source and multi-criteria optimization methods), multi-agent paradigm and adaptive control which show a variety of possible approaches and illustrate the process of students' work. The hardware base has been validated by testing various energy modules and assembling robot using the modules of the proposed kit. The results showed the possibility and potential of studying a variety of interdisciplinary themes using the developed hardware and software complex.